One more way to support Ukraine: Celebrating its endangered biocultural diversity - Stryamets, Nataliya; Khomyn, Igor; Mattalia, Giulia; Prakofjewa, Julia; Pieroni, Andrea; Sõukand, Renata (Ethnobotany Research and Applications, 2022)
Background: Ukraine holds a rich reservoir of cultural and biological diversity due to its complex history and variegated landscapes. However, the current aggression poses threats to it, attacking its identity expressed through local ecological practices. Therefore, in this photo essay, we aim to celebrate the great reservoir of biocultural diversity that we observed during several field investigations in different areas of Ukraine. Methods: We selected photos taken during fieldworks conducted by the authors between 2015 and 2021 in ten oblasts (counties) of Ukraine. The pictures were selected based on their efficacy in conveying a story about a local (food) practice or landscape. Results: Two main aspects of food culture are relevant in Ukraine. First the foraging of wild plants and mushrooms for food and medicinal purposes in forestlands. Second, “babushka markets” where elderly sellers bring a few things they want to sell on the fringes of the official market. They often included preserved as pickles and jams, but also fresh products. In addition, the several traditional Ukrainian landscapes serve as reservoir of biocultural diversity expressed by small-scale farmers and livestock keepers. Conclusions: We illustrated several examples of the richness of the biological and cultural diversity of Ukraine. Nevertheless, freedom is essential for expressing identity through food practices and landscape management. We hope that such a reservoir can serve as a foundation stone for rebuilding destroyed areas and devastated communities. Keywords: Cultural diversity; Ethnobiology; Landscape; Political context; Resistance.